Soil acidobacterial 16S rRNA gene sequences reveal subgroup level differences between savanna-like cerrado and atlantic forest brazilian biomes - Catão, Elisa Caldeira Pires (2014)
16S rRNA sequences from the phylum Acidobacteria have been commonly reported from soil microbial communities, including those from the Brazilian Savanna (Cerrado) and the Atlantic Forest biomes, two biomes that present contrasting characteristics of soil and vegetation. Using 16S rRNA sequences, the present work aimed to study acidobacterial diversity and distribution in soils of Cerrado savanna and two Atlantic forest sites. PCA and phylogenetic reconstruction showed that the acidobacterial communities found in “Mata de galeria” forest soil samples from the Cerrado biome have a tendency to separate from the other Cerrado vegetation microbial communities in the direction of those found in the Atlantic Forest, which is correlated with a high abundance of Acidobacteria subgroup 2 (GP2). Environmental conditions seem to promote a negative correlation between GP2 and subgroup 1 (GP1) abundance. Also GP2 is negatively correlated to pH, but positively correlated to high Al3+ concentrations. The Cerrado soil showed the lowest Acidobacteria richness and diversity indexes of OTUs at the species and subgroups levels when compared to Atlantic Forest soils. These results suggest specificity of acidobacterial subgroups to soils of different biomes and are a starting point to understand their ecological roles, a topic that needs to be further explored.